Estimating the population health burden of musculoskeletal conditions using primary care electronic health records - Yu, D; Peat, G; Jordan, KP; Bailey, J; Prieto Alhambra, D; Robinson, DE; Strauss, VY; Walker-Bone, K; Silman, A; Mamas, M; Blackburn, S; Dent, S; et al. (Oxford University Press, 2021)
Objectives Better indicators from affordable, sustainable data sources are needed to monitor population burden of musculoskeletal conditions. We propose five indicators of musculoskeletal health and assessed if routinely available primary care electronic health records (EHR) can estimate population levels in musculoskeletal consulters.